Determining Factors in Shoulder Pain in Housewives (Boletín Semillero de Investigación en Familia, 2025)
Introduction: Housework has traditionally been attributed to women in their role as homemakers, leading to both physical and mental overload that negatively impacts their well-being. This strain frequently manifests as pain in highly sensitive anatomical structures such as the glenohumeraljoint. Objective: To identify and describe the primary factors associated with shoulder pain in homemakers. Materials and methods: An exploratory study was conducted in two phases: (1) an integrative literature review based on the Whittemore and Knafl methodology, and (2) the design and implementation of a survey instrument incorporating variables derived from the review. A total of 521 women participated, and the data were analyzed using descriptive and correlational statistical techniques. Results: The literature review included 24 studies, from which three thematic categories emerged as relevant to the development of shoulder pain: sociodemographic variables, the nature of housework, and perceived workload. The survey findings revealed statistically significant correlations between shoulder pain and both theduration and frequency of domestic tasks (R ≥ 0.658, p < 0.001). Conclusion: Evidence consistently suggests that prolonged and frequent engagement in housework is directly associated with shoulder pain, often indicating early signs of musculoskeletal injury. Additional influential factors include the woman’s economic conditions and household size. The findings underscore the need to promote collaborative domestic practices, self-care strategies, and efficient task planning as part of targeted interventions aimed at improving women’s health and quality of life.
Keywords: Shoulder Pain; Women’s Health; Housework; Risk Factors; Epidemiology